Agricultural park characteristics and its functions for visitors - Zulkarnain, Izzah Farhana; Mansor, Mazlina (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2017)
Malaysia has obtained its independence since 60 years ago and agriculture has contributed substantially to its gross domestic product. The Malaysian tropical climate is very favourable for the production of various exotic fruits and vegetables, especially since Peninsular Malaysia seldom experiences hurricanes or droughts. Agricultural Park is a unique approach in Malaysia. It was a newly used and implemented term in the country. In addition, agricultural park is famous in overseas rather than in Malaysia. It was first brought by the former Minister of Agriculture back in 1986 in support of the former Prime Minister Tun Mahathir Mohamad. It is the collaboration between agriculture and a park that are combined together to create an agricultural park. Years after the Agricultural Park in Shah Alam was developed, a new project for Agricultural Park was developed in Putrajaya. The uniqueness of the park is that the park lies in the midst of a rapid development of the city in Putrajaya. The locals are introduced with new developments followed by the agricultural elements implemented. The aim of this research is to recommend more attractives design and activities based on the characteristics of the agriculture park. The case study site is at Taman Warisan Pertanian, Putrajaya. This study would identify the issues pertaining to the declining of the visitors of the park using several methods including mixed methods in collecting the data. Once the findings have been obtained, several conclusion and recommendations will be given to improvise the park for the betterment of the society.